Protein Core Fucosylation Regulates Planarian Head Regeneration via Neoblast Proliferation - Wang, Wenjun; Yu, Yuan; Liu, Hongbo; Zheng, Hanxue; Jia, Liyuan; Zhang, Jing; Wang, Xue; Yang, Yang; Chen, Fulin (Frontiers in Cell and Developmental Biology, 2021)
Protein glycosylation is an important posttranslational modification that plays a crucial role in cellular function. However, its biological roles in tissue regeneration remain interesting and primarily ambiguous. In this study, we profiled protein glycosylation during head regeneration in planarian Dugesia japonica using a lectin microarray. We found that 6 kinds of lectins showed increased signals and 16 kinds showed decreased signals. Interestingly, we found that protein core fucosylation, manifested by Lens culinaris agglutinin (LCA) staining, was significantly upregulated during planarian head regeneration. Lectin histochemistry indicated that the LCA signal was intensified within the wound and blastemal areas. Furthermore, we found that treatment with a fucosylation inhibitor, 2F-peracetyl-fucose, significantly retarded planarian head regeneration, while supplement with L-fucose could improve DjFut8 expression and stimulate planarian head regeneration. In addition, 53 glycoproteins that bound to LCA were selectively isolated by LCA-magnetic particle conjugates and identified by LC-MS/MS, including the neoblast markers DjpiwiA, DjpiwiB, DjvlgA, and DjvlgB. Overall, our study provides direct evidence for the involvement of protein core fucosylation in planarian regeneration.